Lattice strain analyses for the L6 ordinary chondrites by the X-ray diffraction method - Imae, Naoya (2019)
The Tenth Symposium on Polar Science/Poster presentations: [OA] Antarctic meteorites, Wed. 4 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object